Tính:
\(A=\sqrt{27}-2\sqrt{48}+3\sqrt{75}\)
\(B=\sqrt{\left(\sqrt{5}-2\right)^2}-\sqrt{\left(\sqrt{5}-3\right)^2}\)
\(C=\sqrt{\left(2\sqrt{3}+1\right)^2}+\sqrt{\left(2\sqrt{3}-5\right)^2}\)
\(D=\sqrt{9-4\sqrt{5}}-\sqrt{14+6\sqrt{5}}\)
\(E=\dfrac{4}{\sqrt{5}-2}-\dfrac{32}{\sqrt{5}+1}\)
\(M=\dfrac{10}{3\sqrt{2}-4}+\dfrac{28}{3\sqrt{2}+2}\)
giúp mình với ạ
\(A=3\sqrt{3}-8\sqrt{3}+15\sqrt{3}=10\sqrt{3}\)
\(B=\left|\sqrt{5}-2\right|-\left|\sqrt{5}-3\right|=\sqrt{5}-2-\left(\sqrt{5}-3\right)=\sqrt{5}-2-\sqrt{5}+3=1\)
\(C=\left|2\sqrt{3}+1\right|+\left|2\sqrt{3}-5\right|=2\sqrt{3}+1+5-2\sqrt{3}=6\)
\(D=\sqrt{\left(\sqrt{5}-2\right)^2}-\sqrt{\left(\sqrt{5}+3\right)^2}=\left|\sqrt{5}-2\right|-\left|\sqrt{5}-3\right|=\sqrt{5}-2-\sqrt{5}+3=1\)
\(E=\frac{4\left(\sqrt{5}+2\right)}{5-4}-\frac{32\left(\sqrt{5}-1\right)}{5-1}=4\sqrt{5}+8-\frac{32\sqrt{5}-32}{4}=4\sqrt{5}+8-8\sqrt{5}+8=16-4\sqrt{5}\)
\(M=\frac{10\left(3\sqrt{2}+4\right)}{18-16}+\frac{28\left(3\sqrt{2}-2\right)}{18-4}=\frac{30\sqrt{2}+40}{2}+\frac{84\sqrt{2}-56}{14}=15\sqrt{2}+20+6\sqrt{2}-4=16+21\sqrt{2}\)